Student Responses to Personal Digital Inquiry (PDI) Learning Integrated with Citizen Science Project (CSP) on Biodiversity Materials in a Senior High School - Mahmudah Nur Cahyaningrum; Topik Hidayat; Kusnadi Kusnadi (Advanced Journal of STEM Education, 2025)
The research was motivated by the fact that biodiversity is declining; therefore, the involvement of all parties, including students, is needed to help save biodiversity. One way to do this is to implement meaningful learning by utilizing the closeness of students and gadgets through the application of personal digital inquiry-integrated citizen science projects in the classroom, which involve experts in carrying out biodiversity conservation projects in the form of a "digital herbarium" uploaded on Instagram. Students’ responses are important as a reference to the extent to which PDI learning integrated with CSP has succeeded. This study aims to analyze students’ responses to Personal Digital Inquiry (PDI) learning integrated with the Citizen Science Project (CSP) on biodiversity material in grade X high school students. This research is a descriptive study using a survey method. Questionnaires were used to collect research data. A total of 42 respondents participated in this study. The questionnaire contains statements about the implementation of learning using six indicators, which were compiled into 34 statements using a Likert scale. The results show a score of 79.73, which is considered good. Students feel enthusiastic and happy to participate in learning, get new experiences interacting with scientists and the surrounding community, increase closeness with teachers and colleagues, and increase awareness to maintain biodiversity by utilizing social media.